The Construction of Historical Empathy in Learning History with a Global Diversity Perspective - Aderoben, Andromeda; Darmawan, Wawan (Indonesian Journal of History Education, 2023)
This study aims to map the ability of historical empathy in learning the history of global diversity. This article adopts qualitative research with literature review method. The steps in this method are: first, identifying the formulation of the problem; second, identifying relevant research; third, selecting studies; fourth, mapping the data; and fifth, compiling, summarizing, and reporting the results. The results of the study describe the definition of historical empathy, the construction of the concept of historical empathy in the formation of the character of global diversity, and the practice of historical empathy with insight into global diversity, which includes relevant learning models, learning resources, and appropriate learning materials. The Learning Model includes introduction, investigation, display, and reflection. Learning resources are recommended through films or museums and must be adapted to learning materials. The implications of this study as a reference material for history teachers in learning design who want to develop historical empathy skills, especially based on global diversity in order to strengthen the character of “Profil Pelajar Pancasila” for students who are tolerant, democratic, open-minded, and critical thinking.